Stereotactic Radiotherapy Ablation and Atrial Fibrillation: Technical Issues and Clinical Expectations Derived From a Systematic Review - Franzetti, Jessica; Volpe, Stefania; Catto, Valentina; Conte, Edoardo; Piccolo, Consiglia; Pepa, Matteo; Piperno, Gaia; Camarda, Anna Maria; Cattani, Federica; Andreini, Daniele; Tondo, Claudio; Jereczek-Fossa, Barbara Alicja; et al. (Frontiers in Cardiovascular Medicine, 2022)
AIM:The purpose of this study is to collect available evidence on the feasibility and efficacy of Stereotactic Arrhythmia Radioablation (STAR), including both Photon RadioTherapy (XRT) and Particle Beam Therapy (PBT), in the treatment of Atrial Fibrillation (AF), and to provide Cardiologists and Radiation Oncologists with a practical overview on this topic. METHODS:Three-hundred thirty-five articles were identified up to November 2021 according to PRISMA criteria; preclinical and clinical studies were included without data restrictions or language limitations. Selected works were analyzed for comparing target selection, treatment plan details and the accelerator employed, addressing workup modalities, acute and long-term side-effects and efficacy, defined either by the presence of scar or the absence of AF recurrence. RESULTS:Twenty-one works published between 2010 and 2021 were included. Seventeen studies concerned XRT, three PBT, one involved both. Nine studies (one in silico and eight in vivo; doses ranging from 15 to 40 Gy) comprised a total of 59 animals, twelve (eight in silico, four in vivo; doses ranging from 16 to 50 Gy) focused on humans, with nine patients undergoing STAR: average follow-up duration was 5 and 6 months, respectively. Data analysis supported efficacy of the treatment in the preclinical setting, whereas in the context of clinical studies the main favorable finding consisted in the detection of electrical scar in 4/4 patients undergoing specific evaluation; the minimum dose for efficacy was 25 Gy in both humans and animals. No acute complication was recorded; severe side-effects related to the long-term were observed only for very high STAR doses in two animals. Significant variability was evidenced among studies in the definition of Target Volume and doses, and in the management of respiratory and cardiac target motion. CONCLUSION:STAR is an innovative non-invasive procedure already applied for experimental treatment of ventricular arrhythmias. Particular attention must be paid to safety, rather than efficacy of STAR, given the benign nature of AF. Uncertainties persist, mainly regarding the definition of the treatment plan and the role of the target motion. In this setting, more information about the toxicity profile of this new approach is compulsory before applying STAR to AF in clinical practice.